2019
DOI: 10.1080/15548627.2019.1586250
|View full text |Cite
|
Sign up to set email alerts
|

TRAF6 inhibits colorectal cancer metastasis through regulating selective autophagic CTNNB1/β-catenin degradation and is targeted for GSK3B/GSK3β-mediated phosphorylation and degradation

Abstract: Aberrant CTNNB1 signaling is one of the fundamental processes in cancers, especially colorectal cancer (CRC). Here, we reported that TRAF6, an E3 ubiquitin ligase important for inflammatory signaling, inhibited epithelial-mesenchymal transition (EMT) and CRC metastasis through driving a selective autophagic CTNNB1 degradation machinery. Mechanistically, TRAF6 interacted with MAP1LC3B/LC3B through its LC3-interacting region 'YxxL' and catalyzed K63-linked polyubiquitination of LC3B. The K63linked ubiquitination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 34 publications
1
61
1
Order By: Relevance
“…One of the novel findings in the present study is that the transcription factors STAT3 and STAT6 could regulate GSK3β/β‐catenin signalling in renal tubular cells (Figure ).This observation, for the first time, unequivocally links intercellular messenger's signals to β‐catenin activation, which would provide broad implications beyond tubular pathology. GSK3β is the serine/threonine protein kinase mediating β‐catenin degradation . Compared with the inhibitors of β‐catenin signalling such as ICG‐001, GSK3β inducers would undoubtedly provide unique inhibition to β‐catenin signalling, as it would trigger the degradation of β‐catenin other than the single inhibition of transcriptional activity.…”
Section: Discussionmentioning
confidence: 99%
“…One of the novel findings in the present study is that the transcription factors STAT3 and STAT6 could regulate GSK3β/β‐catenin signalling in renal tubular cells (Figure ).This observation, for the first time, unequivocally links intercellular messenger's signals to β‐catenin activation, which would provide broad implications beyond tubular pathology. GSK3β is the serine/threonine protein kinase mediating β‐catenin degradation . Compared with the inhibitors of β‐catenin signalling such as ICG‐001, GSK3β inducers would undoubtedly provide unique inhibition to β‐catenin signalling, as it would trigger the degradation of β‐catenin other than the single inhibition of transcriptional activity.…”
Section: Discussionmentioning
confidence: 99%
“…AP2A1 (Tian et al, 2013), Bcl2-L-13 (Murakawa et al, 2015), JIP-1 (Sandilands et al, 2011), SEC62 (Fumagalli et al, 2016), paxillin (Sharifi et al, 2016), SHC1 (Onnis et al, 2018), NUFIP1 (Wyant et al, 2018), NLRX1 (Zhang et al, 2019), JMY (Coutts and La Thangue, 2015), VHL (Kang et al, 2019), TRAF6 (Wu et al, 2019), PHB2 (Wei et al, 2017), PEBP-1 (Noh et al, 2016), optineurin (Rogov et al, 2013), TEX264 (Chino et al, 2019), Trim5α (also known as MURF2B) (Pizon et al, 2013), HGF receptor (also called MET) (Huang et al, 2019), KAT2A (Ouyang et al, 2019), and Fas-apoptotic inhibitory molecule 2 (FAIM2) interact with LC3B via a LIR motif (Jeeyeon et al, 2020). These LIRs were not tested for binding with other ATG8 proteins.…”
Section: Unknown Specificitymentioning
confidence: 99%
“…Tumor necrosis factor receptor–associated factor 6 (TRAF6), a member of the TRAF family, has been identified as a key player in the regulation of inflammation and immunity . Recent studies have indicated that TRAF6 plays critical roles in cancer . Elevated TRAF6 expression is observed in HCC .…”
mentioning
confidence: 99%